Covid-19 Pandemic Effect to Tourism and Strategic to Sustain in Tourism Industry - Jumadi, Jumadi (Technium Social Sciences Journal, 2021)
COVID-19 has influenced the daily lives of people globally. Medical experts confirm that the average number of new infections produced by one infected person is more than five times that of seasonal flu. Covid-19 has the potential to change the way we see the world, how we think, and how we live our lives. This study aims to determine Indonesia Tourism Strategic to Sustain in Covid-19 Pandemic and the company’s strategy to maintain the tourism industry in new normal conditions. This type of research is a literature study with library studies in collecting research data. Data analysis with data reduction, data display is presented in graphical form and is equipped with a descriptive narrative related of the COVID-19 pandemic. The results of this study indicate in the Covid-19 pandemic the tourism industry needed an effective strategy. Tourism and travel business strategies during COVID-19; be transparent, empathize, promote gift cards, provide incentives to customers, invest in CRM infrastructure, prepare retention strategies, look at various possibilities to generate revenue, and use social media. Strategic new normal conditions can be developed in the short-term strategy, medium-term strategy, and long-term strategy.